Implementation of Cascaded based Reversing Voltage Multilevel Inverter using Multi Carrier Modulation Strategies - S. Nagaraja Rao; D. V. Ashok Kumar; Ch. Sai Babu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper, a cascaded based reversing voltage (CBRV) multilevel inverter structure is proposed inorder to compensate the major drawbacks in the conventional multilevel inverters. The proposed topology requires less number of components, less carrier signals and gate drives when compared to existing multilevel inverters particularly at higher levels. Therefore, the complexity and overall cost are greatly reduced particularly for higher output voltage levels. This paper also presents the most relevant control and modulation methods by a triangular based multi carrier pulse width modulation (PWM) scheme for the proposed CBRV inverter topology. This paper presents a comparison between different modulation strategies for CBRV inverter topology based on sinusoidal and space vector references with multi triangular carrier waves. The work strive hard to present the scrutiny that has been made between various PWM control techniques for 1–Ф seven level CBRV inverter structure. The comparison is made in terms of Total Harmonic Distortion (THD) and fundamental RMS voltage. Finally, the simulation results are included to verify the effectiveness of the proposed CBRV inverter topology and validate the proposed theory. A hardware set up was developed for a 1–Ф seven level CBRV inverter topology using FPGA based pulse generation.